Diseño e implementación de un sistema de inventarios para la constructora Ciudadela del Café S.A.S en la ciudad de Armenia Quindío (2013)
The internship is a Design and implementation of a inventory system for the construction Company Ciudadela del Cafe S.A.S. the problem arises from the need to give the company the most appropriate management and process to provide the personnel a tool for better performance. The realization of the design and implementation of a system inventory is planned for specific targets that were raised, allowing to reach the general objective proposed. Building it on theoretical bases defined that were reviewed and analyzed in orden to adjust to the demands of work.